Garimpo de ouro e cooperativismo no Brasil: formalização e dispersão geográfica da atividade garimpeira - Alan Ferreira de Freitas; Jean de Jesus Peres; Alair Ferreira de Freitas; Samuel Soares da Silva (Confins)
The objective of this article is to understand how socioeconomic and legal-institutional factors are contributing to evidence the expansion of cooperativism in gold mining in Brazil, demonstrating an overview of these organizations in the country and signaling to their reality. Data from mining requests made available by the National Mining Agency were accessed and analyzed those made by cooperatives. The results of this work are presented in two broad categories: (i) Overview of mining concessions for mineral cooperatives, which show the intense movement of application for gold mining area, especially in the Amazon, conducted by miners' cooperatives; and (ii) Densification and geographical dispersion of mineral cooperatives in Brazil, which signal the exponential expansion of mining requisitions for gold mining by cooperatives between 2019 and 2022, organizations and their dispersion to different regions of Brazil. The price of gold and the easing of the gold mining legislation in Brazil interfered widely in this movement of mineral cooperatives. Despite the expansion of the demand for gold mining made by cooperatives, this movement does not mean strengthening the social organization of miners/ miners and this suggests the importance of this research agenda and the need for its continuity.